Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.15244/pjoes/70231
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Sodalite by Geopolymerization Process Using Coal Fly Ash

Abstract: IntroductionGeopolymers, also called inorganic polymers, are classified as synthetic aluminosilicate materials characterized by many interesting properties. This group of materials has gained a lot of attention in the past 10 years (measured by increasing number of publications) and raised high expectations concerning their applicability. Geopolymers are usually hard, mechanically resistant materials, therefore many attempts to substitute Portland cement in the construction industry have been taken [1]. Despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 24 publications
(30 reference statements)
0
4
0
2
Order By: Relevance
“…Compared with GEO, two additional vibration peaks were observed in the ZEO spectrum after hydrothermal treatment. These were the vibration peak at 874 cm −1 , which was the stretching vibration of Si–O–Si, and the symmetric stretching of zeolite tetrahedron at 712 cm −1 , which is one of the characteristic peaks of zeolite molecular sieves 13 , 37 . At the same time, it was observed that after hydrothermal treatment, the peak at 984 cm −1 shifted to 996 cm −1 , which was caused by the increasing degree of active aluminum cross-linking and the degree of silico-aluminate gel polymerization 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Compared with GEO, two additional vibration peaks were observed in the ZEO spectrum after hydrothermal treatment. These were the vibration peak at 874 cm −1 , which was the stretching vibration of Si–O–Si, and the symmetric stretching of zeolite tetrahedron at 712 cm −1 , which is one of the characteristic peaks of zeolite molecular sieves 13 , 37 . At the same time, it was observed that after hydrothermal treatment, the peak at 984 cm −1 shifted to 996 cm −1 , which was caused by the increasing degree of active aluminum cross-linking and the degree of silico-aluminate gel polymerization 38 .…”
Section: Resultsmentioning
confidence: 99%
“…De acordo com a intensidade dos picos, verifica-se que o quartzo é mais frequente, seguido de mulita e hematita. Esta mineralogia também foi evidenciada por KRÓL et al [40] e por AZEVEDO et al [41]. Mesmo sendo de locais distintos, observou-se semelhanças entre os difratogramas principalmente no halo amorfo e no pico de quartzo que fica entre 26° e 27º [38][39][40][41].…”
Section: Resultsunclassified
“…Esta mineralogia também foi evidenciada por KRÓL et al [40] e por AZEVEDO et al [41]. Mesmo sendo de locais distintos, observou-se semelhanças entre os difratogramas principalmente no halo amorfo e no pico de quartzo que fica entre 26° e 27º [38][39][40][41]. A formação da mulita, identificada somente por DRX, está relacionada com a combustão do carvão em temperaturas maiores do que 1050°C.…”
Section: Resultsunclassified
“…It can be observed that the Si-O-T (T:Si or Al) stretching vibration, centered on the precursor at 1035 cm −1 , shifted to lower frequencies in the geopolymers (1004-994 cm −1 ). This change also indicates that the geopolymerization reaction has taken place due to the activation of the amorphous phase of the SOBE residue with the formation of N-A-S-H aluminosilicate gel, which means the condensation of Si-O tetrahedra as well as SiO 4 and AlO 4 in the geopolymer [40,[68][69][70]. The band shift at lower frequencies may be due to an increase in the content of non-bridging oxygens, as well as to an increase in the amount of tetrahedral aluminum in the gel structure [27,71].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 97%